PENINGKATAN HASIL BELAJAR MELALUI PEMANFAATAN LINGKUNGAN SEBAGAI SUMBER BELAJAR IPA SISWA KELAS V SEKOLAH DASAR - Dharmawati Dharmawati (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This research aims to improve student learning outcomes through environmental exploitation. This research is categorical action research that is carried out in one cycle or cycles. The stages in each cycle are planning, implementation, observation and reflection. The research points are students of category V SDN 146 or X Tanjung Solok, totaling 20 people. The object includes science learning outcomes. Research information is combined using test and monitoring methods. The test is used to obtain information about the results of students' science practice. Monitoring is used to dig up information about students' activities in exploring science learning, then the combined information is analyzed quantitatively and qualitatively. Science learning through the use of the environment as a learning resource is very helpful for students in science learning, using the environment as a learning resource can increase teacher motivation and get a positive response from students which has an effect on increasing student learning outcomes.